2018
DOI: 10.11137/2018_3_395_412
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and Litogeochemistry Analyses of Massangana, São Carlos and Caritianas Massifs belonging to Youngest Granites of the Rondonia Tin Province

Abstract: A Suíte Intrusiva Rondônia (990 a 998 Ma) é representada por um magmatismo tipo-A rapakivítico que ocorreu no SW do Cráton Amazonas com mineralizações em Sn, Nb, Ta, W e topázio associadas. Este estudo apresenta dados petrográicos e litogeoquímicos dos Maciços Massangana, São Carlos e Caritianas, integrantes da Suíte Intrusiva Rondônia com o objetivo de caracterizar a petrograia e geoquímica destes maciços para melhor compreender sua evolução magmática. As amostras analisadas são granitoides de granulação gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The later system was characterized by deformation and recrystallization of syn-to late-tectonic granites, including the rapakivi granites from 1.6 to 1.51 Ga (Serra da Providência Suite), in addition to felsic volcanism and sedimentation between 1.5 and 1.4 Ga. Between 1.5 and 1.35 Ga, there is a period of stability in the Rio Negro-Juruena Province, characterized by a distensional tectonic regime with the generation of mega fractures that allowed the accommodation of the anorogenic granitic suites of Santo Antônio, Teotônio, and Alto Candeias, in addition to basic and ultrabasic rocks, sedimentation of continental rifts [49][50][51][52][53][54][55][56][57][58][59].…”
Section: Geological Context Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The later system was characterized by deformation and recrystallization of syn-to late-tectonic granites, including the rapakivi granites from 1.6 to 1.51 Ga (Serra da Providência Suite), in addition to felsic volcanism and sedimentation between 1.5 and 1.4 Ga. Between 1.5 and 1.35 Ga, there is a period of stability in the Rio Negro-Juruena Province, characterized by a distensional tectonic regime with the generation of mega fractures that allowed the accommodation of the anorogenic granitic suites of Santo Antônio, Teotônio, and Alto Candeias, in addition to basic and ultrabasic rocks, sedimentation of continental rifts [49][50][51][52][53][54][55][56][57][58][59].…”
Section: Geological Context Of the Study Areamentioning
confidence: 99%
“…Rapakivi granite intrusive suites in Rondônia Tin Province have been extensively studied in recent decades [49][50][51][52][53][54][55][56][57][58][59]. Despite being primarily anorogenic, new studies [62,63] have shown that distal relationships with orogenic events may play an important role in forming these suites.…”
Section: The Petrogenesis Of the Massangana Massifmentioning
confidence: 99%